Assessing interobserver variability and accuracy in the histological diagnosis and classification of cutaneous neurofibromass. (5th December 2019) - Ortonne, Nicolas; Carroll, Steven L; Rodriguez, Fausto J; Miller, Douglas C; Nazarian, Rosalynn M; Blakeley, Jaishri O; Madaj, Zachary B; Verma, Sharad K; Stemmer-Rachamimov, Anat
Abstract: Background: Cutaneous neurofibromas (cNFs) are the most common tumors in people with neurofibromatosis type 1 (NF1) and are associated with reduced quality of life. There is currently no widely accepted standardized language for describing cNFs clinically or histopathologically. The objective of this study was to evaluate interobserver agreement across pathologists in describing and reporting of neurofibromas involving the skin. Methods: Twenty-eight (H&E)-stained slides of cNF were scanned using an Aperio XT scanner. The digital images were reviewed by 6 pathologists, who entered free text of up to a 200 word description for each case into a REDcap database. Responses were analyzed for the most commonly used terms based on frequency, as well as agreement (reported as concordance) between reviewers. Results: A set of the terms most commonly used by pathologists for the histological classification of cNF along with areas of agreement and disagreement have been identified. The study shows that there was strong agreement across reviewers that not all neurofibromas involving the skin are cutaneous neurofibromas and regarding the presence or absence of atypical features and heterologous elements. Areas of less concordance were identified and include cNF subtypes, definition of extension and pattern of growth, as well as the distinction of a cNF from a plexiform without an intraneural component involving skin. Conclusions: This work is the first step towards development of a robust classification system and devising "gold standard" histopathologic diagnostic criteria for cutaneous neurofibromas.